A previously unidentified circRNA inhibits virus replication by regulating the miR-24-3p/KEAP1 axis. - Haimin Li; Liuyang Du; Juan Li; Yanming Huang; Chenhe Lu; Tingjuan Deng; Yan Yan; Yulan Jin; Wei Wu; Jinyan Gu; Jiyong Zhou (PLoS Pathogens)
Circular RNAs (circRNAs) exert diverse biological functions in different processes. However, the role of circRNAs during virus infection is mostly unknown. Herein, we explored the characteristics of host circRNAs using alphaherpesvirus pseudorabies virus (PRV) as a model. PRV infection upregulated the expression of circRNA circ29164, which does not encode a protein. RNA pulldown assays identified that circ29164 interacts with the microRNA ssc-miRNA-24-3p. Further analysis indicated that ssc-miR-24-3p targets the mRNA encoding kelch-like ECH-associated protein 1 (KEAP1), and circ29164 competitively binds to ssc-miR-24-3p to prevent it binding to Keap1. Apoptosis detection demonstrated that circ29164 or Keap1 overexpression, but not knockdown, induced caspase 3 activity and the release of cytochrome C from mitochondria, and inhibited PRV replication. Taken together, these data identified a previously undiscovered circRNA, circ29164, which inhibits PRV replication by competitively binding to ssc-24-3p to maintain KEAP1 levels.